2005
DOI: 10.1084/jem.20051239
|View full text |Cite
|
Sign up to set email alerts
|

The human macrophage mannose receptor directs Mycobacterium tuberculosis lipoarabinomannan-mediated phagosome biogenesis

Abstract: Mycobacterium tuberculosis (M.tb) survives in macrophages in part by limiting phagosome–lysosome (P-L) fusion. M.tb mannose-capped lipoarabinomannan (ManLAM) blocks phagosome maturation. The pattern recognition mannose receptor (MR) binds to the ManLAM mannose caps and mediates phagocytosis of bacilli by human macrophages. Using quantitative electron and confocal microscopy, we report that engagement of the MR by ManLAM during the phagocytic process is a key step in limiting P-L fusion. P-L fusion of ManLAM mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
441
1
7

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 449 publications
(459 citation statements)
references
References 61 publications
10
441
1
7
Order By: Relevance
“…After phagocytosis, Mtb blocks phagosome acidification as well acquisition of hydrolytic enzymes and anti‐microbial peptides. Two major Mtb virulence factors are involved in the blockage of the phagosomal maturation in human cell lines: the glycolipid lipoarabinomannan (LAM) (Hmama et al ., 2004; Kang et al ., 2005; Welin et al ., 2008) and the secreted tyrosine phosphatase (PtpA) (Bach et al ., 2008; Wong et al ., 2011; Wong and Jacobs, 2011). Mtb lacking the surface lipid trehalose dimycolate (TDM) failed to block phagosome maturation in mouse macrophages (Katti et al ., 2008) but to date, this has not been shown in human cells.…”
Section: Cell Autonomous Defence Mechanisms In Tbmentioning
confidence: 99%
“…After phagocytosis, Mtb blocks phagosome acidification as well acquisition of hydrolytic enzymes and anti‐microbial peptides. Two major Mtb virulence factors are involved in the blockage of the phagosomal maturation in human cell lines: the glycolipid lipoarabinomannan (LAM) (Hmama et al ., 2004; Kang et al ., 2005; Welin et al ., 2008) and the secreted tyrosine phosphatase (PtpA) (Bach et al ., 2008; Wong et al ., 2011; Wong and Jacobs, 2011). Mtb lacking the surface lipid trehalose dimycolate (TDM) failed to block phagosome maturation in mouse macrophages (Katti et al ., 2008) but to date, this has not been shown in human cells.…”
Section: Cell Autonomous Defence Mechanisms In Tbmentioning
confidence: 99%
“…43,44 This pathogen adaptation may allow metacyclic parasites to be briefly present extracellularly after introduction into the host via the vector sand fly, protecting the parasite from complement lysis but also providing a reduced proinflammatory response than would otherwise occur without LPG glycocalyx folding. The trimannose cap on ManLAM has been shown to engage MR, prevent phagolysosomal maturation, 45 and, thus, lead to similar reduced cytokine production. We demonstrated that trimannose-coated beads inhibited IL12p40 through an MR-mediated mechanism, which may help balance signaling mediated through other lectin receptors 36 and allow intracellular survival of M. tuberculosis in macrophages.…”
Section: Pathogen Mechanisms For Deterrence Of Oligosaccharide-mediatmentioning
confidence: 99%
“…Phosphatidylcholine accounts to 75% of total phospholipid [85] GP Viral envelopes are enriched in sphingomyelin [8,86] SP Envelope cholesterol is critical for structure and infectivity [87][88][89] ST 2 Phosphatidylserine stimulates entry of enveloped viruses [90,91] Mannose receptor binds to the ManLAM mannose caps of mycobacteria and mediates phagocytosis [92] GPI anchored proteins (host [35,36] and parasite [37] …”
Section: Glmentioning
confidence: 99%